2018
DOI: 10.3390/molecules23030555
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme Kinetics and Molecular Docking Studies on Cytochrome 2B6, 2C19, 2E1, and 3A4 Activities by Sauchinone

Abstract: Sauchinone, an active lignan isolated from the aerial parts of Saururus chinensis (Saururaceae), exhibits anti-inflammatory, anti-obesity, anti-hyperglycemic, and anti-hepatic steatosis effects. As herb–drug interaction (HDI) through cytochrome P450s (CYPs)-mediated metabolism limits clinical application of herbs and drugs in combination, this study sought to explore the enzyme kinetics of sauchinone towards CYP inhibition in in vitro human liver microsomes (HLMs) and in vivo mice studies and computational mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 50 publications
(79 reference statements)
0
6
0
Order By: Relevance
“…It has been reported that the amino acid residues of Phe57, Phe108, Ile120, Leu211, Phe241, Ile301, Phe304, Ile369, Leu373, Arg105, Leu364, Arg365, Leu366, Phe367, Pro368, Ala370, Met371, Arg372 and Glu374 in CYP3A4 played a key role in ligand binding 38‐44 . Another study suggested that Phe57, Arg105, Arg106, Phe108, Phe215, Met371, Arg372, Leu373, Glu374 and Arg375 were involved in interaction between sauchinone and CYP3A4 protein 45 . Figure 5 indicated that Hem508, Arg105 and Glu374 amino acid residues interacts with SSd via hydrogen bond interactions at a distance of 2.88Å, 3.13Å and 3.21Å, respectively, while Ser119 was bonded at the distance of 2.81 Å and 3.18 Å. Hydrophobic interaction between SSd and CYP3A4 was formed with Phe57, Phe215, Asp76, Gly481, Leu373, He369, Thr309, Leu482, Phe304, He301, He120, Phe108, Arg106, Phe213 and Arg372 residues and SSd was prone to bind to amino acid residues in the A chain of the CYP3A4 protein.…”
Section: Discussionmentioning
confidence: 98%
“…It has been reported that the amino acid residues of Phe57, Phe108, Ile120, Leu211, Phe241, Ile301, Phe304, Ile369, Leu373, Arg105, Leu364, Arg365, Leu366, Phe367, Pro368, Ala370, Met371, Arg372 and Glu374 in CYP3A4 played a key role in ligand binding 38‐44 . Another study suggested that Phe57, Arg105, Arg106, Phe108, Phe215, Met371, Arg372, Leu373, Glu374 and Arg375 were involved in interaction between sauchinone and CYP3A4 protein 45 . Figure 5 indicated that Hem508, Arg105 and Glu374 amino acid residues interacts with SSd via hydrogen bond interactions at a distance of 2.88Å, 3.13Å and 3.21Å, respectively, while Ser119 was bonded at the distance of 2.81 Å and 3.18 Å. Hydrophobic interaction between SSd and CYP3A4 was formed with Phe57, Phe215, Asp76, Gly481, Leu373, He369, Thr309, Leu482, Phe304, He301, He120, Phe108, Arg106, Phe213 and Arg372 residues and SSd was prone to bind to amino acid residues in the A chain of the CYP3A4 protein.…”
Section: Discussionmentioning
confidence: 98%
“…FKA shows obvious inhibition of different CYP isoforms, and subsequent inhibition experiments showed that CYP3A2 was the primary isoform contributing to the metabolism of FKA. Gong et al ( 2018 ) performed a molecular docking experiment to study the binding mode between sauchinone and CYPs. The results showed the interactions of sauchinone in the active site of CYP2B6, 2C19, 2E1, and 3A4.…”
Section: Applicationsmentioning
confidence: 99%
“…During this process, the "lock-key" principle of ligand-receptor interaction and the principle of "induction fit" by computer pattern recognition and optimization techniques are adopted respectively (Lohning et al, 2017). According to a large number of studies, computer-aided drug screening has managed to seek the best molecule combination, which has achieved success in active botanical components virtual screening and drug targets discorvery (Wang et al, 2017;Gong et al, 2018;Zihad et al, 2018;Saikia and Bordoloi, 2019). In this case, with the development of bioinformatics technology, it has become possible to extract the differentially expressed genes for specific diseases from open databases when conducting comprehensive research (Liang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%